Beyond the "Bereitschaftspotential": Action preparation behind cognitive functions. (July 2017) - Di Russo, F.; Berchicci, M.; Bozzacchi, C.; Perri, R.L.; Pitzalis, S.; Spinelli, D.
Highlights: We review EEG literature on motor-related cortical activity of the last 10 years. The focus is on the brain proactive cognitive control for complex interactive actions. Prefrontal, frontal, parietal and insular cortices are involved in action planning. In brain preparation phase, we can catch glimpses of cognitive functions foundation. Abstract: Research on preparatory brain processes taking place before acting shows unexpected connections with cognitive processing. From 50 years, we know that motor-related brain activity can be measured by electrocortical recordings 1–3 s before voluntary actions. This readiness potential has been associated with increasing excitably of premotor and motor areas and directly linked to the kinematic of the upcoming action. Now we know that the mere motor preparation is only one function of a more complex preparatory activity. Recent research shows that before any action many cognitive processes may occur depending on various aspects of the action, such as complexity, meaning, emotional valence, fatigue and consequences of the action itself. In addition to studies on self-paced action, the review considers also studies on externally-triggered paradigms showing differences in preparation processes related to age, physical exercise, and task instructions. Evidences from electrophysiological and neuroimaging recording indicate that in addition to the motor areas, the prefrontal, parietal and sensory cortices may be active during action preparation to anticipate future events and calibrate responses.